2017
DOI: 10.1038/s41551-017-0077
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the pre-metastatic niche

Abstract: The pre-metastatic niche — the accumulation of aberrant immune cells and extracellular matrix proteins in target organs — primes the initially healthy organ microenvironment and renders it amenable for subsequent metastatic cell colonization. By attracting metastatic cancer cells, mimics of the pre-metastatic niche offer both diagnostic and therapeutic potential. However, deconstructing the complexity of the niche by identifying the interactions between cell populations and the mediatory roles of the immune sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 139 publications
0
111
0
Order By: Relevance
“…We hypothesized that delivery of these cytokines would alter the recruitment of circulating tumor cells. Thus, we next investigated the effect of immunomodulatory cytokine delivery on tumor cell abundance in implanted scaffolds (Figure ) that have previously been shown to recruit tumor cells at this implant site and time scale (Aguado et al, ; Aguado et al, ; Aguado et al, ; Aguado et al, ; Azarin et al, ; Rao et al, ) with an experimentally determined detection limit of five tumor cells in 250,000 total cells (0.002%) by flow cytometry (Azarin et al, ). We found that IL10 significantly reduced the percentage of tdTomato+4T1 metastatic tumor cells spontaneously arriving at the scaffold relative to FLUC (0.06 ± 0.03% tdTomato+ of total cells for IL10, 0.13 ± 0.04% tdTomato+ for FLUC, 0.09 ± 0.02% tdTomato+ for CCL2, and 0.11 ± 0.04% tdTomato+ for CXCL12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that delivery of these cytokines would alter the recruitment of circulating tumor cells. Thus, we next investigated the effect of immunomodulatory cytokine delivery on tumor cell abundance in implanted scaffolds (Figure ) that have previously been shown to recruit tumor cells at this implant site and time scale (Aguado et al, ; Aguado et al, ; Aguado et al, ; Aguado et al, ; Azarin et al, ; Rao et al, ) with an experimentally determined detection limit of five tumor cells in 250,000 total cells (0.002%) by flow cytometry (Azarin et al, ). We found that IL10 significantly reduced the percentage of tdTomato+4T1 metastatic tumor cells spontaneously arriving at the scaffold relative to FLUC (0.06 ± 0.03% tdTomato+ of total cells for IL10, 0.13 ± 0.04% tdTomato+ for FLUC, 0.09 ± 0.02% tdTomato+ for CCL2, and 0.11 ± 0.04% tdTomato+ for CXCL12).…”
Section: Resultsmentioning
confidence: 99%
“…In this report, we hypothesized that local modulation of the immune microenvironment could serve as a means to influence tumor cell abundance and to dissect the contribution of specific immune cell populations to the recruitment of tumor cells to a metastatic site. Biomaterials that recruit metastatic cancer cells in vivo are an emerging technology to investigate tumor cell abundance and phenotype at a premetastatic niche (Aguado et al, ; Aguado et al, ; Aguado et al, ; Aguado et al, ; Azarin et al, ; Bersani et al, ; Ko et al, ; J. Lee et al, ; Rao et al, ). First, they provide a defined site in vivo to which tumor cells are recruited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that before the cancer metastasis occurs, the primary tumors actively and selectively modify the future metastatic sites in which tumor‐secreted factors and tumor‐shed extracellular vesicles facilitate the recruitment of myeloid cells to establish an amenable microenvironment for incoming cancer cells . Moreover, the predetermined microenvironment, called the pre‐metastatic, niche plays a vital role in determining the fate and survival of CTCs and subsequent metastatic cell homing and colonization .…”
Section: Microfluidic Platforms For Engineered Tumor Microenvironmentmentioning
confidence: 99%
“…Moreover, the predetermined microenvironment, called the pre‐metastatic, niche plays a vital role in determining the fate and survival of CTCs and subsequent metastatic cell homing and colonization . Basically, the complex pre‐metastatic niche involves in the mediatory roles of the soluble factors, stromal cells, immune cells, and ECM proteins, as well as interactions between cell populations . Tumor‐secreted factors recruit bone‐marrow‐derived cells (BMDCs) to the pre‐metastatic niche in which the factors interact with the local stroma to form amenable sites for metastatic cells .…”
Section: Microfluidic Platforms For Engineered Tumor Microenvironmentmentioning
confidence: 99%
“…For example, pancreatic cancer cell-secreted exosomes have been shown to accumulate in secondary tissues such as the liver and lead to the generation of pre-metastatic niches through activating hepatic stellate cells and Kupffer cells to drive ECM remodelling 243 and can be detected in the circulating blood, offering promise of potential biomarker applications. Given the technical limitations of studying these early pre-metastatic events in vivo and in the clinic, there has recently been a push to develop engineered niche-mimicking biomaterials to better study this process 247, 248 .…”
Section: Building New Homes: Metastatic Seeding and Tissue Colonisationmentioning
confidence: 99%